Using Feedback Panels to Analyze a Web Site's Target Audiences - Pat Melgares (Journal of Applied Communications, 2005)
Colleges and universities develop Web sites to help them recruit and retain students, connect with alumni and donors, and communicate internally, among other activities. In 2004, the faculty and staff in Kansas State University’s Department of Animal Sciences and Industry completed a redesign of its Web site, partially based on findings of two online surveys completed by members of nine target audiences. This feedback approach allowed a communications working group to acquire marketing data quickly and reliably. The working group used this information to address usability concerns and design a site with features that target audiences want. The results indicate that Web users prefer functionality over visual appeal and less cluttered sites. This approach to gathering feedback provides opportunities for continuing analyses of Web user groups, including longitudinal studies with the same group or comparison studies with new members of the same user groups.